La PUISIFY The Form of Application-Based Poetry Learning Media SAC.2.0 on Android - Dewi Kusumaningsih; Bety Ayu Windi Ariyanto; Haryanti Budi Utami; Krisna Adi Ismaya (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The study highlights the development of poetry learning instrument using Smart Application Creator (SAC) 2.0 program for Android. The study belongs to a Research and Development (RnD). The initial exploration included the observation of the Indonesian Language learning instrument utilized by a number of secondary schools which are the former education institutions of the students of Indonesian Language and Literature Department (PBSI) of University of Veteran Bangun Nusantara Sukoharjo. The result of observation became the underlying framework for the development of poetry learning instrument through the SAC 2.0 program for Android. The design of the learning instrument development refered to the four-D model development that consists of four stages, including define, design, develop, and disseminate. The development model was firstly developed by Thiagarajan, dkk. The findings revealed that Android-based learning instrument had yet been massively utilized for secondary schools. Most of the teachers still rely on the PowerPoint presentation which is displayed through the projector. The development of the learning instrument that refers to the 4D stages has successfully provided an innovative Android-based poetry learning instrument. The instrument has also been disseminated publicly. The new learning instrument is easy in its installation and application through Android devices. Keywords: android, learning instrument, poetry instrument, smart application creator 2.0. Abstrak Penelitian ini mengangkat pengembangan media pembelajaran puisi dengan menggunakan program Smart Aplication Creator 2.0 berbasis andoid. Bentuk penelitian adalah Research and Development (RnD). Eksplorasi awal dengan pengamatan penggunaan media pembelajaran Bahasa Indonesia di SMA-SMA alumni para mahasiswa Progdi Pendidikan Bahasa dan Sastra Indonesia (PBSI) FKIP Universitas Veteran Bantara. Hasil pengamatan dipakai sebagai dasar pengembangan media pembelajaran bahasa Indonesia khususnya puisi dengan aplikasi SAC 2.0 di android. Model pengembangan dalam merancang dan membuat media pembelajaran puisi berbasis android ini menggunakan model pengembangan four-D models yang terdiri dari 4 tahap yaitu Define (pendefinisian), Design (perancangan), Develop (pengembangan) dan Dessiminate (penyebaran). Model pengembangan ini dikembangkan oleh Thiagarajan, dkk. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis andriod di SMA belum digunakan. Guru masih menggunakan media pembelajaran power point serta proyektor saja. Proses pengembangan model media pembelajaran dilakukan sesuai 4 langkah D berhasil membuat inovasi media pembelajaran puisi berbasis adroid yang sudah diseminasikan pada publik. Model media pembelajaran ini mudah diinstal dan diaplikasikan di telepon genggam berbasis android. Kata kunci: andriod, media pembelajaran, media puisi, smart aplication creator 2.0.